2022
DOI: 10.1108/jmd-10-2021-0290
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of knowledge management on talent management and firm performance in small and medium enterprise in Uganda

Abstract: PurposeThis study examines the mediating effect of an effective knowledge management (KM) in the relationship between talent management (TM) and organizational performance. This study was operationalized among the small and medium enterprises (SMEs).Design/methodology/approachA cross-sectional survey design was used to collect data from a sample of 260 SMEs business. The data collected was analyzed using correlations and hierarchical regression to test the mediating effect of KM on the relationship between TM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…In a recent study by Correia et al (2022) in Portugal established the mediating role of DCs on firm performance. Bagorogoza and Nakasule (2022), in their study on the mediating effect of KM on talent management and firm performance in small and medium enterprise in Uganda, they found out that KM mediates the relationship between talent management and performance. Shujahat et al (2019) in their study on translating the impact of KM processes into Knowledge-based innovation: the neglected and mediating role of knowledge-worker productivity.…”
Section: Km Mediate the Relationship Between The Hpo Framework And Pe...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study by Correia et al (2022) in Portugal established the mediating role of DCs on firm performance. Bagorogoza and Nakasule (2022), in their study on the mediating effect of KM on talent management and firm performance in small and medium enterprise in Uganda, they found out that KM mediates the relationship between talent management and performance. Shujahat et al (2019) in their study on translating the impact of KM processes into Knowledge-based innovation: the neglected and mediating role of knowledge-worker productivity.…”
Section: Km Mediate the Relationship Between The Hpo Framework And Pe...mentioning
confidence: 99%
“…Particularly, the performance of knowledge-intensive business services such as FIs is largely dependent on the successful management of organisational knowledge (Obeidat et al, 2016). In the study by (Bagorogoza and Nakasule, 2022;and Hassana and Raziqb, 2019), they found out that there is a relationship between KM and performance in small and medium enterprises. The relevance of knowledge and its effective and efficient management for organisational performance seems to be a widely accepted issue in most of existing management literature (Andreava and Kianto, 2012;Inkinen, 2015).…”
Section: Knowledge Management and High Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, customer KM acts as a mediator in the relationship between knowledge-oriented leadership and innovation quality (Chaithanapat et al , 2022). KM can mediate the relationship between TM and organisational performance (Bagorogoza and Nakasule, 2022). KM processes were found to partially mediate the relationship between high performance work systems and intrapreneurial behaviour (Portalanza-Chavarría and Revuelto-Taboada, 2023).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…We looked at the challenge of a biased sample. (Bagorogoza, 2022) Organizational Performance and Human Talent Management variables, with a total of 26 publications in the Scopus database. In the same way, it was established that the application of theories framed in the area of Business, Management and Accounting, were used more frequently in the implementation of the development and management of human talent since this part of the organization to improve organizational performance, taking into account this important factor, it is necessary to have a much more critical and dynamic thinking since the bases of these contribute to the success of the organization.…”
Section: Co-occurrence Of Wordsmentioning
confidence: 99%